Aerodynamics at the heart of performance - Hill, G. (Sports Performance & Tech, 2015)
Aerodynamics have become one of the cornerstones of several sports today. Formula 1 teams fight to have the most aerodynamic cars, athletes wear skin tight lycra and cyclists wear skin suits so tight that they need assistance just to put them on.With the importance of down force and smooth airflow, we look at what difference it actually makes in sport.